The Analysis of Influence Growth Sales and Fixed Asset Intensity on Tax Avoidance: English - Mutiara Lusiana Annisa Annisa; Astro Yudha Kertarajasa; Ruth Samantha Hamzah; Efva Octavina Donata Gozali; Christian Damar Sagara Sitepu (Enrichment : Journal of Management, 2023)
The study examines the effect of sales growth and fixed asset intensity on tax avoidance in automotive companies listed on the Indonesian Stock Exchange. Research on the effect of sales growth and fixed asset intensity on tax avoidance in automotive companies listed on the Indonesia Stock Exchange has several urgent needs to be considered. Following are some of the reasons why this research is important: Tax avoidance by automotive companies can have a significant impact on state revenues. If companies reduce their tax obligations illegally, this can reduce state revenues that should be used for development and the provision of public services. Furthermore, automotive companies listed on the Indonesia Stock Exchange have an important economic role in the growth and development of the country. In order to maintain the sustainability and transparency of this sector, it is important to understand the possible tax avoidance practices of these companies.The sampling method used purposive sampling with a sample of manufacturing companies in the automotive sector listed on the Indonesian Stock Exchange in the period of 2020 to 2022. Based on the sampling method, 10 companies were obtained as samples, thus there were 30 firms year observations. The analysis method employed multiple linear regression. The results show that sales growth and fixed asset intensity have no effect on tax avoidance. This result encourages companies to carry out tax planning properly to fulfill tax obligations efficiently and effectively in accordance with the tax provisions set by the government, so that the tax revenue target is successfully obtained and the number of tax avoidance declines.